Case Report: Discovery a Novel SARS-CoV-2 Variant in a Six-Months Long-Term Swab Positive Female Suffering From Non-Hodgkin Lymphoma - Capoluongo, Ettore; Nardelli, Carmela; Esposito, Maria Valeria; Buonomo, Antonio Riccardo; Gelzo, Monica; Pinchera, Biagio; Zappulo, Emanuela; Viceconte, Giulio; Portella, Giuseppe; Setaro, Mario; Gentile, Ivan; Castaldo, Giuseppe (Frontiers in Oncology, 2021)
Background: We report the case of a woman with non-Hodgkin lymphoma who remained positive on the molecular assay for SARS-CoV-2 for six months: she has never experienced a severe form of COVID-19 although in absence of seroconversion. Methods: The whole SARS-CoV-2 genome analysis was performed by the CleanPlex SARS-CoV-2 Research and Surveillance NGS Panel (PARAGON GENOMICS, Hayward, USA). Results: we found twenty-two mutations in SARS-CoV-2 genome and a novel deleterious ORF3a frameshift c.766_769del corresponding to a unique and novel lineage. The region affected by this frameshift variant is reported as being important in determining SARS-CoV-2 immunogenicity. Patient’s immunophenotype showed the absence of B lymphocytes and significantly reduced T-cell count. Only after the treatment with hyperimmune plasma she finally became negative on the swab. Conclusions: Our findings could be helpful in the management of patients with immunodeficiency, particularly when novel variants, potentially altering the virus immune-response, are present.